Agriculture and ritual landscape: A case study from the Magars of Argal, Baglung District, Nepal - Khattri, Man Bahadur (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 2,357 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v8i0.1123 Occasional Papers in Sociology and Anthropology Vol.8 2003 p.88-104